Tolerance to occasional frosts during germination in Chilean Altiplano quinoa (Chenopodium quinoa Willd.) cultivars - Yurin, Ignacio Delfino; Delatorre-Herrera, José; Rodríguez, Juan Pablo; Delatorre-Castillo, José Pablo; Sepúlveda-Soto, Isabel; Low-Pfeng, Cristopher (Frontiers in Plant Science, 2026)
Quinoa (Chenopodium quinoa Willd.) is increasingly cultivated in marginal environments; however, early-season frosts pose a major constraint to successful stand establishment. Despite evidence of genotypic variation in cold tolerance, the effects of short, occasional frost events occurring at specific germination stages remain poorly understood. We evaluated the impact of single, occasional frost events (0, −2, and −4 °C) applied during distinct germination phases: Phase I (imbibition, 4 h), Phase II (absorption, 2 h), and Phase III (radicle protrusion, 6 h), in two Chilean quinoa cultivars (Roja and Amarilla). Across four replicates (50 seeds per cultivar per treatment), we quantified germination percentage and rate, imbibition rate, osmotic potential (Φ), and proline content under controlled conditions. The main results were: Frost exposure during Phases I and II markedly reduced final germination, frequently causing reductions greater than 70% relative to the control, with the strongest inhibition observed at −4 °C during Phase I. In contrast, when frost was applied during Phase III, germination was less affected and generally remained above 50%, indicating clear phase-dependent tolerance. Frost conditions reduced imbibition rate and induced a more negative osmotic potential, accompanied by increased proline accumulation, particularly at −4 °C during Phases II and III. Amarilla showed higher germination than Roja when frost was applied during Phase III, revealing cultivar-specific responses. These findings demonstrate that the first hours following sowing constitute a critical sensitivity window to occasional frost in quinoa. Phase-specific physiological responses, including osmotic adjustment, appear to play a protective role under freezing stress. The observed cultivar differences highlight exploitable genetic variation and provide valuable information for improving sowing management and breeding strategies under increasing climatic variability.